Iterative solution of the fractional Wu-Zhang equation under Caputo derivative operator - Yasmin, Humaira; Alderremy, A. A.; Shah, Rasool; Hamid Ganie, Abdul; Aly, Shaban (Frontiers in Physics, 2024)
In this study, we employ the effective iterative method to address the fractional Wu-Zhang Equation within the framework of the Caputo Derivative. The effective iterative method offers a practical approach to obtaining approximate solutions for fractional differential equations. We seek to provide insights into its solution and behavior by applying this method to the Wu-Zhang Equation Through numerical analysis and the presentation of relevant tables and Figures, we demonstrate the accuracy and efficiency of this method in solving the fractional Wu-Zhang Equation. This research contributes to the understanding and solution of fractional-order differential equations and their applications in various scientific and engineering domains.